Efficient Generation of Gene‐Modified Pigs Harboring Precise Orthologous Human Mutation via CRISPR/Cas9‐Induced Homology‐Directed Repair in Zygotes. Issue 1 (23rd October 2015) - Zhou, Xiaoyang; Wang, Lulu; Du, Yinan; Xie, Fei; Li, Liang; Liu, Yu; Liu, Chuanhong; Wang, Shiqiang; Zhang, Shibing; Huang, Xingxu; Wang, Yong; Wei, Hong
Abstract : Without inhibition of non‐homologous end joining (NHEJ) pathways and using single strand oligo DNA (ssODN) as templates, we efficiently generated gene‐modified pigs harboring precise orthologous human mutation via CRISPR/Cas9‐induced homology‐directed repair (HDR) in zygotes with an efficiency as high as 80%. Besides, we found that a higher concentration of ssODN remarkably reduced HDR‐derived mutation efficiency, suggesting that the activities of HDR relative to NHEJ were reduced with the higher amounts of ssODN. ABSTRACT: Precise genetic mutation of model animals is highly valuable for functional investigation of human mutations. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated 9 (Cas9)‐induced homology‐directed repair (HDR) is usually used for precise genetic mutation, being limited by the relatively low efficiency compared with that of non‐homologous end joining (NHEJ). Although inhibition of NHEJ was shown to enhance HDR‐derived mutation, in this work, without inhibition of NHEJ, we first generated gene‐modified pigs harboring precise orthologous human mutation ( Sox10 c.A325>T) via CRISPR/Cas9‐induced HDR in zygotes using single‐strand oligo DNA (ssODN) as template with an efficiency as high as 80%, indicating that pig zygotes exhibited high activities of HDR relative to NHEJ and were highly amendable to genetic mutation via CIRSPR/Cas9‐induced HDR. Besides, we found a higher concentration of ssODN remarkably reduced HDR‐derived mutation in pig zygotes, suggesting a possible balance for optimal HDR‐derived mutation in zygotes between the excessive accessibility to HDR templates and the activities of HDR relative to NHEJ which appeared to be negatively correlated to ssODN concentration. In addition, the HDR‐derived mutation, as well as those from NHEJ, extensively integrated into various tissues including gonad of founder pig without detected off‐targeting, suggesting CRISPR/Cas9‐induced HDR in zygotes is a reliable approach for precise genetic mutation in pigs.